Notas sobre urbanidade: um paralelo temporal entre o Centro e o Altiplano - Melo, Myllena Miliann Silva (2019)
This research is interested in the Public open spaces (POS) of the Downtown and Altiplano districts, in the city of João Pessoa, and seeks to investigate its current spatial configurations and social dynamics, in the light of the concept of urbanity. The POS are constituted as stages that promote the relations of the social sphere in the spatial sphere, “[bringing together] an infinity of Urban Technical and Spatial Devices”. At disposal in the urban environment, the elements that compound the POS serves to the publics, being orchestrated by the set of companies and the organizations responsible for constituting a liveable city.In this sense, the POS are central to the discussion of urbanity and are considered “instruments of urbanity” (ibidem). This theme approaches on issues related to the built environment of the city, which, driven by private initiative and its marketing logic, has resulted in urban environments that are insufficiently alive and poorly understood by city audiences. It is a mercantilist production of POS essentially based on projects that deepen the rationalization of the urban space, also partially responsible for the dilution of the public space. These findings stimulate a field of research interested in measures and modalities of action, capable of mitigating the effects of the current urban fabrication. The question of insecurity or the repercussion of these feelings in the patterns of use of the POS are still the object of this research, since they promote the desertification of the spaces, collaborating for their segregation and / or underutilization. Thus, this research aims to investigate the patterns of urbanity in Public Open Spaces of the downtown and Altiplano neighborhoods, from a contrast of this concept with different epistemological postures, as well as from categories of analysis built within the physical and social dimensions of objects.